Economic analysis of the use of holmium enucleation of the prostate and laparoscopic simple prostatectomy in the surgical treatment of large-volume prostatic hyperplasia - S. N. Volkov; D. Yu. Pushkar; K. B. Kolontarev; V. S. Stepanchenko; V. I. Tereshchenko; A. R. Dzharimok; A. E. Shevyakina; M. A. Daurov (Вестник урологии, 2024)
Introduction. The method of choice for surgical treatment of benign prostatic hyperplasia (BPH) with a volume of more than 80 сс is holmium enucleation of the prostate (HoLEP). However, laser enucleation of the prostate is associated with limitations that carry both a clinical and financial burden. Laparoscopic simple prostatectomy (LSP) has now emerged as an alternative to transurethral procedures. In addition to ensuring clinical efficacy, optimal approaches to surgical management of large-volume BPH must also be financially viable, which underlines the significance of this study.Objective. To conduct a comparative economic analysis of holmium laser enucleation of the prostate and laparoscopic retropubic simple prostatectomy combined with temporary clamping of the internal iliac arteries and vesicourethral anastomosis (LSP + TCA + VUA).Materials & methods. An economic analysis of the results of HoLEP (214 people) and LSP + TCA + VUA (215 people) was conducted in a multicenter, open-label study. The economic analysis aimed to calculate the direct costs associated with surgery, as well as indirect costs related to hospitalization. A comparative analysis of drug prescriptions was conducted, including an assessment of costs for conservative treatment during hospitalization and the postoperative period. The economic losses associated with the duration of patients' temporary disability were calculated as the total loss in gross domestic product (GDP) production.Results. The cost of basic surgical equipment was 15,701,000.0 and 36,927,827.0 rubles (₽) for LSP + TCA + VUA and HoLEP, respectively. The median direct costs for performing LSP + TCA + VUA and laser enucleation HoLEP was 54,990.6 [49,870.5; 67,850.8] and 69,158.9 [65,005.9; 72,351.7] ₽, respectively. The median of indirect costs in the LSP + TCA + VUA and HoLEP groups was 71,251.0 [68,039.0; 73,103.0] and 80,451.0 [74,423.0; 83,501.0] ₽, respectively. The indicators of lost profits in GDP production per person were 5,398.4 and 6,167.9 ₽ in the LSP + TCA + VUA and HoLEP groups, respectively.Conclusion. The rationale for the use of LPA + VPA + UCA in the surgical treatment of large-volume BPH is based on economically justified advantages compared with HoLEP.